2020
DOI: 10.1186/s12885-020-07423-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of tissue elasticity in the differential diagnosis of benign and malignant breast lesions using shear wave elastography

Abstract: Background Elastography is a promising way to evaluate tissue differences regarding stiffness, and the stiffness of the malignant breast lesions increased at the lesion margin. However, there is a lack of data on the value of the shear wave elastography (SWE) parameters of the surrounding tissue (shell) of different diameter on the diagnosis of benign and malignant breast lesions. Therefore, the purpose of our study was to evaluate the diagnostic performance of shell elasticity in the diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
(38 reference statements)
2
13
1
Order By: Relevance
“…Our study offered the automatically plotted 1-3 mm shells around the breast lesion, which helped to calculate the maximum YM at the tumor border. However, unlike previous studies [20,[23][24][25], our results revealed that the presence of the stiff rim sign had the highest diagnostic accuracy rather than those quantitative SWE parameters, especially the E max of 1-3mm shell. We supposed that this is because the shell, which is composed of glandular tissue, may also exist around benign tumors, thus affecting the diagnostic performance of the E max at the shell [12].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study offered the automatically plotted 1-3 mm shells around the breast lesion, which helped to calculate the maximum YM at the tumor border. However, unlike previous studies [20,[23][24][25], our results revealed that the presence of the stiff rim sign had the highest diagnostic accuracy rather than those quantitative SWE parameters, especially the E max of 1-3mm shell. We supposed that this is because the shell, which is composed of glandular tissue, may also exist around benign tumors, thus affecting the diagnostic performance of the E max at the shell [12].…”
Section: Discussioncontrasting
confidence: 99%
“…The desmoplastic reaction caused by the peritumoral infiltration of cancer cells into the interstitial tissues increases the peritumoral stiffness 9 , 21 , 22 . Recent studies using this shell-based analysis found that the E max of 1-3mm shell was the most accurate for differential diagnosis of benign and malignant breast lesions 20 , 23 - 25 . Our study offered the automatically plotted 1-3 mm shells around the breast lesion, which helped to calculate the maximum YM at the tumor border.…”
Section: Discussionmentioning
confidence: 99%
“…From these displacements on the acoustic axis, we can evaluate the wave phase velocity component (WPVC) of the low frequency induced wave on the acoustic axis at different depths. Thus, It will be possible to derive values for the shear elastic modulus from this parameter in isotropic or transversely isotropic media, approximately one third of the Young's modulus of the medium in soft tissues (Soleimani et al, 2020;Yang et al, 2020;Chen et al, 2018;Skerl et al, 2016b;Suhail et al, 2019). However, the well-known expression of said modulus is no longer valid for triclinic media and, furthermore, a mathematical expression…”
Section: Experimental Method: 1d Transient-ultrasonic Speckle Interferometrymentioning
confidence: 99%
“…Diverse techniques are used to study mechanical properties of tumors, including optical measurements, cantilevers, elastography (Fovargue et al, 2020), and pre-stressed surfaces (Staunton et al, 2016), but additional research on these and new techniques is still needed to understand the cell-microenvironment mechanical interaction. Recent literature describes the relationship between malignant lesions and anisotropy of breast cancer confirmed that malignant lesions are more anisotropic than benign (Sinkus et al, 2001;Skerl et al, 2016aSkerl et al, , 2016bGu et al, 2020;Böl et al, 2014;Soltaninezhad et al, 2020;Soleimani et al, 2020;Yang et al, 2020;Chen et al, 2018). In 2001, R. Sinkus et al observed a tendency of breast tumors to be anisotropic (Sinkus et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Data were retrospectively collected from April 2018 to May 2020. The sample size calculation was based on previously published studies, with an expected sensitivity of 0.8 and an expected specificity of 0.9 used in the final calculation (15)(16)(17). Alpha (α) was 0.05, with an allowable error of 10%.…”
Section: Study Design and Patient Enrollmentmentioning
confidence: 99%